Scaffold Protein Lnx1 Stabilizes EphB Receptor Kinases for Synaptogenesis - Li, Na; Chen, Si; Xu, Nan-Jie; Sun, Suya; Chen, Jin-Jin; Liu, Xian-Dong (Frontiers in Molecular Neuroscience, 2022)
Postsynaptic structure assembly and remodeling are crucial for functional synapse formation during the establishment of neural circuits. However, how the specific scaffold proteins regulate this process during the development of the postnatal period is poorly understood. In this study, we find that the deficiency of ligand of Numb protein X 1 (Lnx1) leads to abnormal development of dendritic spines to impair functional synaptic formation. We further demonstrate that loss of Lnx1 promotes the internalization of EphB receptors from the cell surface. Constitutively active EphB2 intracellular signaling rescues synaptogenesis in Lnx1 mutant mice. Our data thus reveal a molecular mechanism whereby the Lnx1-EphB complex controls postsynaptic structure for synapse maturation during the adolescent period.